2008
DOI: 10.1007/s11111-008-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Demarcating forest, containing disease: land and HIV/AIDS in southern Zambia

Abstract: The ongoing HIV/AIDS pandemic in southern Africa continues to manifest itself in unexpected ways. While the consequences of the disease appear straightforward in some aspects-e.g., medical, labor, cost-in other respects the repercussions, while large, are nonetheless highly nuanced and can be counterintuitive. This paper reports on the intersection of HIV/AIDS, migration, livelihood adaptation, land tenure, and forest conservation, to outline how adaptation to the pandemic has reworked significant aspects of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…In Zambia, for example, women widowed by AIDS have worked in concert with an opening created by statutory law and the chiefs to build a case for retaining land ownership -challenging customary law that favored relatives of the deceased male head of household (Frank and Unruh 2008). Post-conflict situations may create opportunities for women to claim stronger rights, either where they have played a major role in peacemaking and rebuilding (as in Rwanda and Liberia) or because high widowhood rates make it more critical to provide women with control of resources to secure livelihoods and household wellbeing (Hunt and Posa 2001;Powley 2003).…”
Section: Promote Dialogue and Negotiation To Resolve Resource Conflictsmentioning
confidence: 99%
“…In Zambia, for example, women widowed by AIDS have worked in concert with an opening created by statutory law and the chiefs to build a case for retaining land ownership -challenging customary law that favored relatives of the deceased male head of household (Frank and Unruh 2008). Post-conflict situations may create opportunities for women to claim stronger rights, either where they have played a major role in peacemaking and rebuilding (as in Rwanda and Liberia) or because high widowhood rates make it more critical to provide women with control of resources to secure livelihoods and household wellbeing (Hunt and Posa 2001;Powley 2003).…”
Section: Promote Dialogue and Negotiation To Resolve Resource Conflictsmentioning
confidence: 99%
“…In Zambia, for example, women widowed by AIDS have worked in concert with an opening created by statutory law and the chiefs to build a case for retaining land ownership-challenging customary law as practiced by the relatives of the deceased male head of household (Frank and Unruh 2008). Postconflict situations may create opportunities for women to claim stronger rights, either where they have played a major role in peacemaking and rebuilding (as in Rwanda and Liberia) or because high widowhood rates make it more critical to provide women with control of resources (Hunt and Posa 2001;Powley 2003).…”
Section: Promote Dialogue and Negotiation To Resolve Resource Conflictsmentioning
confidence: 99%
“…For example, a study from Zambia has suggested that HIV/AIDS shocks can open up new opportunities for some groups, and may even provide a catalyst through which community-based natural resource management initiatives are strengthened rather than weakened. 21 Moreover, studies which adjust for household income level when exploring HIV/AIDS effects on natural resource use have suggested that HIV/AIDSattributable events, such as mortality in adults of prime age, may result in an increased use of natural resources by households affected by HIV/AIDS -but only if those households have sufficiently high income to cover the costs of collecting, processing and delivering these goods to local markets. 8,13 In addition to financial capital, household human and physical capital may also play a role in moderating the use of natural resources following an HIV/AIDS-related event.…”
Section: Hiv/aids and Use Of Natural Resourcesmentioning
confidence: 99%